Faktor yang Mempengaruhi Rendahnya Kualitas Pendidikan di Indonesia - Baidah Baidah; Mislaini Mislaini; Damilsi Hijaya (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Education is one of the efforts to improve the quality of human resources. The purpose of this study is to examine the current poor quality of education in Indonesia. Indeed, education is something that is agreed upon as the main concern of every nation. The quality of education of a nation is one of the determinants of the progress of a nation. In other words, the progress of a nation or country can be measured by the quality of education of that nation or country. This research uses descriptive qualitative research. Literature research is used as the method. The author collects information from newspapers and books that are believed to be true and relevant to the discussion of this article. According to the results of the study, education in Indonesia is still of low quality. The low quality of education in Indonesia can be attributed to the many educational problems faced by Indonesia. These problems are classified into two types, namely macro education problems, which consist of confusing and overly complicated curricula, unequal education, costs, teacher placement, and poor teacher quality. The problems with microscopy are the monotonous method, inappropriate equipment and infrastructure, and poor student performance. The discussion includes several solutions that are expected to solve Indonesia's education problems and Indonesia can improve the quality of its education so that it can be compared or even outperformed by other countries. This letter is expected to increase the awareness of each individual to build a better and more advanced Indonesia to prepare quality human beings.